Tolerability of inhaled N-chlorotaurine in an acute pig streptococcal lower airway inflammation model - Schwienbacher, Martin; Treml, Benedikt; Pinna, Anna; Geiger, Ralf; Reinstadler, Hannes; Pircher, Iris; Schmidl, Elisabeth; Willomitzer, Christian; Neumeister, Johannes; Pilch, Michael; Hauer, Maria; Hager, Thomas; et al. (BMC infectious diseases, 2011)
Inhalation of N-chlorotaurine (NCT), an endogenous new broad spectrum non-antibiotic anti-infective, has been shown to be very well tolerated in the pig model recently. In the present study, inhaled NCT was tested for tolerability and efficacy in the infected bronchopulmonary system using the same model.
Gesehen am 31.10.2022